2005
DOI: 10.1021/jo051722h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Symmetrical Organic Carbonates via Significantly Enhanced Alkylation of Metal Carbonates with Alkyl Halides/Sulfonates in Ionic Liquid

Abstract: [reaction: see text] We report a new phosgene-free method for the synthesis of symmetrical organic carbonates via alkylation of metal carbonate with various alkyl halides and sulfonates in 1-n-butyl-3-methylimidazolium hexafluorophosphate, [bmim][PF6], as an ecofriendly reaction media. Alkylation of metal carbonate in various ionic liquids with 1-bromo-3-phenylpropane (1a) as a model reactant has thoroughly been investigated. Potassium and cesium carbonates appeared to be the most suitable metal carbonate due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Excellent yields may be obtained by running the reaction at 383 K in ionic liquids such as imidazolium salts, offering the advantage of simple experimental and work -up procedures [46] . An alternative route from CO 2 , alcohols and alkyl halides is also effective by the addition of a strong base (e.g., substituted guanidines), so as to trap the hydrogen chloride that is formed [47] .…”
Section: Direct Routementioning
confidence: 99%
“…Excellent yields may be obtained by running the reaction at 383 K in ionic liquids such as imidazolium salts, offering the advantage of simple experimental and work -up procedures [46] . An alternative route from CO 2 , alcohols and alkyl halides is also effective by the addition of a strong base (e.g., substituted guanidines), so as to trap the hydrogen chloride that is formed [47] .…”
Section: Direct Routementioning
confidence: 99%
“…1 Nowadays, the applications of IL are rapidly increased. An amount of literature has reported the wide use of IL as extractant for liquid-liquid extraction, [2][3][4][5][6] solvent for organic synthesis, [7][8][9][10][11] catalyst for some reactions [12][13][14][15] and so on. The adjustable property of IL via combination of different cations or anions has attracted researchers' attention and thus plenty of new task-specific ILs were synthesized for particular applications.…”
Section: Introductionmentioning
confidence: 99%
“…After 1-ethyl-3-methylimidazolium tetrafluoroborate, the first air-and water-stable IL, was reported, [4] several ILs have been synthesized because of their many attractive features, such as negligible vapor pressure, noncombustibility, ionic conductivity and wide-ranging electrochemical potential. These characteristics have encouraged researchers to devise various applications, such as environmentally friendly solvents for chemical syntheses, [5][6][7][8][9][10][11][12] phase separations at lower critical temperatures, [13] new-type actuators, [14][15][16][17][18] non-volatile electrolytes for lithium ion batteries, [19][20][21][22][23][24] fuel cells, [25][26][27] and solar batteries. [28][29][30] It was recently reported that very slow vaporization of some ILs is detected under high vacuum and high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%